Severe Thyrotoxicosis Secondary to Povidone-Iodine from Peritoneal Dialysis - Kirstie Lithgow; Christopher Symonds (Case Reports in Endocrinology)
A 73-year-old male on home peritoneal dialysis (PD) with recent diagnosis of atrial fibrillation presented with fatigue and dyspnea. Hyperthyroidism was diagnosed with TSH < 0.01 mIU/L and FT4 > 100 pmol/L. He had no personal or family history of thyroid disease. There had been no exposures to CT contrast, amiodarone, or iodine. Technetium thyroid scan showed diffusely decreased uptake. He was discharged with a presumptive diagnosis of thyroiditis. Three weeks later, he had deteriorated clinically. Possible iodine sources were again reviewed, and it was determined that povidone-iodine solution was used with each PD cycle. Methimazole 25 mg daily was initiated; however, he had difficulty tolerating the medication and continued to clinically deteriorate. He was readmitted to hospital where methimazole was restarted at 20 mg bid with high dose prednisone 25 mg and daily plasma exchange (PLEX) therapy. Biochemical improvement was observed with FT4 dropping to 48.5 pmol/L by day 10, but FT4 rebounded to 67.8 pmol/L after PLEX was discontinued. PLEX was restarted and thyroidectomy was performed. Pathology revealed nodular hyperplasia with no evidence of thyroiditis. Preoperative plasma iodine levels were greater than 5 times the upper limit of normal range. We hypothesize that the patient had underlying autonomous thyroid hormone production exacerbated by exogenous iodine exposure from a previously unreported PD-related source.